Animal feed research in eastern and southern Africa: Historical and actual priorities - Jutzi, S.C.; Tothill, J.C. (New Zealand Grassland Association, 1993)
A review of animal feed research Reports from 7 countries of eastern and southern Africa is used to assess historical and actual research emphases. Priority was on feed supply and evaluation for cattle production with strong rangelands improvement programmes. Most research focussed on ecologically favoured regions and larger-scale livestock commodity production. Strong efforts for the exploitation of grasses for improved feed supply were supported by legume work for feed quality improvement. There was a strong emphasis on feed agronomy work, one third of all that work involving animals. Component research results were Reported with little discussion of target systems implications, and very little of this knowledge was generated on-farm. Only 1 in 4 Reports on feed research explicity linked this research to the animal exerting the demand for such feed. The concept of key-farming was extensively dealt with. Multi-purpose tree and crop residue work was given a secondary profile. There was a decisive re-orientation of animal feed research after independence to cater for the needs of smallholder livestock agriculture, with substantially strengthened emphasis on legumes, crop-livestock integration, multipurpose trees, zero grazing, and on small-stock feeding.